Isavuconazole and voriconazole for the treatment of chronic pulmonary aspergillosis: A retrospective comparison of rates of adverse events. Issue 3 (15th January 2019) - Bongomin, Felix; Maguire, Niamh; Moore, Caroline B.; Felton, Timothy; Rautemaa‐Richardson, Riina
Summary: Background: Long‐term oral triazole antifungal therapy is the cornerstone of management for patients with chronic pulmonary aspergillosis (CPA). Itraconazole is the first‐line choice of treatment. Voriconazole, posaconazole or isavuconazole can be used as alternative treatments in case of resistance or intolerance. All of these can cause significant adverse drug reactions. Objectives: To evaluate how CPA patients tolerate voriconazole and isavuconazole after prior triazole therapy. Methods: We performed a retrospective observational study at the UK National Aspergillosis Centre. Medical records for all consecutive CPA patients started on isavuconazole and voriconazole during an observation period of 12 and 6 months respectively were analysed. Results: During this study period, 20 patients were started on isavuconazole and 21 patients on voriconazole. Adverse events were seen in 18 of 21 (86%) the patients in the voriconazole group and 12 of 20 (60%) in the isavuconazole group ( P  = 0.02). For those who developed adverse events to these agents, the rates of discontinuation of therapy were comparable (ie 10/18 [56%], voriconazole vs 8/12 [67%], isavuconazole; P  = 0.54). Five (25%) patients in the isavuconazole group who were intolerant to other triazoles tolerated the standard dose of isavuconazole. Conclusions: Compared with isavuconazole, adverse events were significantly higher in CPA patients commenced on voriconazole. Isavuconazole may be an option for those patients who are intolerant to other triazoles.